Job Autonomy and Job Involvement: Do They Influence Each Other in the Work from Home System? - Hadi, Irma Surya; Harahap, Farida (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Post-pandemic, the world of work has undergone a major shift toward more flexible systems, where the boundaries between personal and professional life have become increasingly blurred. In this new work landscape, employee engagement has emerged as a key element in maintaining productivity and sustaining performance. One factor believed to play a significant role in enhancing engagement is job autonomy, which allows employees to manage how, when, and by what standards they complete their tasks. The study aims to determine the canonical relationship between a set of job autonomy variables consisting of work method autonomy, work schedule autonomy, and work criteria autonomy with job involvement variables, namely job involvement role and job involvement setting, in employees who work from home. This research adopts a quantitative method with a survey approach and a correlational design. Data were collected online through the distribution of an online questionnaire on social media, involving 252 respondents who were selected using a self-selection sampling technique. Data were collected using two psychological scales: the Job Autonomy Scale and the Job Involvement Scale. The validity of the instrument was obtained through expert judgment from two expert lecturers and a scale trial. The reliability of the job involvement scale was demonstrated by Cronbach’s Alpha, which was 0.966, while the job autonomy scale had an alpha of 0.960. The data analysis technique employed was canonical correlation analysis. The results of the analysis indicate a significant canonical relationship between the dimensions of job autonomy and job involvement, with all multivariate statistics (Pillai’s Trace, Hotelling’s Trace, and Wilks’ Lambda) showing significant results (p < 0.001). The relationship is positive, meaning that the higher the perceived job autonomy, the higher the employee’s involvement, both in terms of role and environmental aspects. Based on the canonical loadings, the dimension of criterion autonomy contributed the most to the job autonomy set (1.916), while role involvement made the highest contribution to the job involvement set (11.272). These findings emphasize that having flexibility in determining performance benchmarks and actively engaging in work roles are key factors in enhancing overall employee involvement. Pasca pandemi, dunia kerja mengalami pergeseran besar menuju sistem yang lebih fleksibel, di mana batas antara kehidupan pribadi dan profesional semakin kabur. Dalam lanskap kerja baru ini, keterlibatan kerja menjadi elemen kunci yang menentukan produktivitas dan keberlanjutan kinerja karyawan. Salah satu faktor yang diyakini berperan penting dalam memperkuat keterlibatan tersebut adalah otonomi kerja, yang memberi ruang bagi karyawan untuk mengelola cara, waktu, dan tolok ukur keberhasilan dalam menyelesaikan tugasnya. Penelitian ini bertujuan untuk mengetahui hubungan kanonik antara set variabel otonomi kerja yang terdiri atas otonomi metode kerja, otonomi jadwal kerja, dan otonomi kriteria kerja dengan set variabel keterlibatan kerja, yaitu keterlibatan kerja peran dan keterlibatan kerja lingkungan, pada karyawan yang bekerja dari rumah (work from home). Penelitian ini merupakan penelitian kuantitatif dengan pendekatan survei dan desain korelasional. Data dikumpulkan secara daring melalui penyebaran kuesioner online di media sosial, dengan melibatkan 252 responden yang dipilih menggunakan teknik self-selection sampling. Data dikumpulkan menggunakan dua skala psikologis, yaitu skala otonomi kerja dan skala keterlibatan kerja. Validitas instrumen diperoleh melalui expert judgment dua dosen ahli serta uji coba skala. Reliabilitas skala keterlibatan kerja menunjukkan nilai cronbach’s alpha sebesar 0.966, sedangkan skala otonomi kerja sebesar 0.960. Teknik analisis data menggunakan analisis korelasi kanonik. Hasil analisis menunjukkan adanya hubungan kanonik yang signifikan antara dimensi otonomi kerja dan keterlibatan kerja, dengan seluruh statistik multivariat (Pillai’s Trace, Hotelling’s Trace, dan Wilks’ Lambda) signifikan pada p < 0.001. Hubungan ini bersifat positif, artinya semakin tinggi otonomi kerja yang dirasakan karyawan, maka semakin tinggi pula keterlibatan mereka dalam pekerjaan, baik dari aspek peran maupun lingkungan. Berdasarkan hasil canonical loadings, dimensi otonomi kriteria kerja memberikan kontribusi tertinggi terhadap set otonomi kerja (1.916), sedangkan keterlibatan kerja peran menjadi penyumbang terbesar pada set keterlibatan kerja (11.272). Temuan ini menegaskan bahwa keleluasaan dalam menentukan tolok ukur keberhasilan serta keterlibatan aktif dalam peran kerja merupakan faktor penting dalam meningkatkan keterlibatan karyawan secara keseluruhan.